2022
DOI: 10.1186/s12888-021-03671-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of Covid-19 pandemic-related stress and depressive symptoms among international medical students

Abstract: Background The outbreak of Covid-19 had negative impacts on the mental stress and induced psychological distress among university students worldwide. This study proposed a moderated mediation model, and hypothesized that the Covid-19 pandemic-related stress was positively related to depressive symptoms among international medical students. Methods An online survey on stress and depressive symptoms of international students was conducted in a medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 54 publications
(62 reference statements)
4
15
0
1
Order By: Relevance
“…Results of the present study support Hypotheses 1a and 1b, suggesting that students’ stresses related to COVID-19 and the “social event” positively predicted depression. This observation is in line with the existing literature arguing that COVID-19-related stress or stressors were associated with increased depression in adolescents ( Ellis et al, 2020 ) and university students ( Rudenstine et al, 2021 ; Lu et al, 2022 ). However, it is noteworthy that there are inconsistent findings in the literature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results of the present study support Hypotheses 1a and 1b, suggesting that students’ stresses related to COVID-19 and the “social event” positively predicted depression. This observation is in line with the existing literature arguing that COVID-19-related stress or stressors were associated with increased depression in adolescents ( Ellis et al, 2020 ) and university students ( Rudenstine et al, 2021 ; Lu et al, 2022 ). However, it is noteworthy that there are inconsistent findings in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…In adolescents, Ellis et al (2020) reported that COVID-19 stress was associated with increased loneliness and depressive symptoms. In college students, Lu et al (2022) found that COVID-19 stress was positively associated with symptoms of depression. Galanza et al (2021) showed that COVID-19-related fear predicted three mental illness indicators, including depression, stress, and anxiety.…”
Section: Literature Reviewmentioning
confidence: 98%
“…14 Supporting our hypothesis, these meta-analysis findings could indicate that international students who perceived higher levels of pandemic related stress may have had a negative impact on their academic performance in medical school. 15 . However, even though mental health IJMS was a common theme, it was only listed in responses as 27.3% for the international students and 1.7% for the United States students.…”
Section: Discussionmentioning
confidence: 99%
“…This finding also confirms our hypothesis and current literature, that perceived social support is a protective factor and influences the mental health status of the medical student. 15 It is worth noting, United States medical students had political critiques of how COVID was handled at the beginning of the pandemic which was not seen in the international responses. As reported, the government plays an important role in reducing mental health disparities with efficient intervention and appropriate policy changes.…”
Section: Discussionmentioning
confidence: 99%
“…Relevance of the topic was formulated in times of COVID-19 pandemic, as it brought additional stress to people. For example, this perceived stress can negatively impact learning engagement and academic outcomes of university students (Lu et al, 2022;Sfeir et al, 2022). At the same time, mindfulness can become a regulator that helps reduce the level of perceived stress (Castillo-Sánchez et al, 2022;Xu et al, 2022).…”
Section: Justification Of the Choice Of Articles And Goals And Object...mentioning
confidence: 99%